2015
DOI: 10.3233/wor-141894
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of workplace violence on psychiatric staff

Abstract: BACKGROUND A study by Hesketh et al. found that 20% of psychiatric nurses were physically assaulted, 43% were threatened with physical assault, and 55% were verbally assaulted at least once during the equivalent of a single work week. From 2005 through 2009, the U.S. Department of Justice reported that mental health occupations had the second highest average annual rate of workplace violence, 21 violent crimes per 1,000 employed persons aged 16 or older. OBJECTIVE An evaluation of risk factors associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
2
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 42 publications
1
79
2
3
Order By: Relevance
“…One study found that up to 99% of psychiatric ward (PW) healthcare providers reported that they had experienced verbal violence from patients or their families, and approximately 70% had been physically assaulted by patients in the past 12 months [4]. A similar study showed that PW nurses experienced an average incidence of verbal and physical violence of 0.6 and 0.19 times per nurse per week, respectively [5]. One study reported that physical and psychological violence were experienced annually by 55.7% and 82.1% of the PW nurses in Taiwan, respectively [6].…”
Section: Introductionmentioning
confidence: 99%
“…One study found that up to 99% of psychiatric ward (PW) healthcare providers reported that they had experienced verbal violence from patients or their families, and approximately 70% had been physically assaulted by patients in the past 12 months [4]. A similar study showed that PW nurses experienced an average incidence of verbal and physical violence of 0.6 and 0.19 times per nurse per week, respectively [5]. One study reported that physical and psychological violence were experienced annually by 55.7% and 82.1% of the PW nurses in Taiwan, respectively [6].…”
Section: Introductionmentioning
confidence: 99%
“…Ridenour et al . () found no differences between days of the week with regard to violent occurrences. However, working the day shift increased the risk of exposure to verbal violence, and working the evening shift increased the risk of exposure to physical violence.…”
Section: Discussionmentioning
confidence: 84%
“…Also, patient restriction, physical assistance, and medication were reasons for violent behaviour especially in inpatient settings (Ridenour et al . ). Ose et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations